2009
DOI: 10.1063/1.3183945
|View full text |Cite
|
Sign up to set email alerts
|

Plasma parameters of pulsed-dc discharges in methane used to deposit diamondlike carbon films

Abstract: Here we approximate the plasma kinetics responsible for diamondlike carbon ͑DLC͒ depositions that result from pulsed-dc discharges. The DLC films were deposited at room temperature by plasma-enhanced chemical vapor deposition ͑PECVD͒ in a methane ͑CH 4 ͒ atmosphere at 10 Pa. We compared the plasma characteristics of asymmetric bipolar pulsed-dc discharges at 100 kHz to those produced by a radio frequency ͑rf͒ source. The electrical discharges were monitored by a computer-controlled Langmuir probe operating in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 63 publications
3
11
0
Order By: Relevance
“…Our previous work using asymmetric RF discharges with methane (CH 4 ) has also revealed a linear range over a broad parameter field up to a sheath voltage of 500 V and down to a pressure of 4 Pa, conditions at which ion energies up to 100 eV are easily generated 51, 53. Similar results were obtained by Corbella et al54, 55 For hydrocarbon plasmas, it could be demonstrated that mainly plasma chemistry affects the deposited mass over a broad parameter range yielding dense barrier coatings 49, 56–59…”
Section: Resultssupporting
confidence: 82%
“…Our previous work using asymmetric RF discharges with methane (CH 4 ) has also revealed a linear range over a broad parameter field up to a sheath voltage of 500 V and down to a pressure of 4 Pa, conditions at which ion energies up to 100 eV are easily generated 51, 53. Similar results were obtained by Corbella et al54, 55 For hydrocarbon plasmas, it could be demonstrated that mainly plasma chemistry affects the deposited mass over a broad parameter range yielding dense barrier coatings 49, 56–59…”
Section: Resultssupporting
confidence: 82%
“…[51,53] Similar results were obtained by Corbella et al [54,55] For hydrocarbon plasmas, it could be demonstrated that mainly plasma chemistry affects the deposited mass over a broad parameter range yielding dense barrier coatings. [49,[56][57][58][59] Despite the fact that the same apparent activation energy is obtained for both experimental series shown in Figure 3, the actual mass deposition rate per monomer flow is seen to vary with the actual C 2 H 4 flow rate.…”
Section: à5supporting
confidence: 76%
“…Gas discharges are widely used in such various fields as etching and deposition of films, [1,2] surface treatment, [3] ozone generation, [4] bio-sterilization, [5] fusion, [6] and thrusters. [7] Currently, most of the plasma sources are operated at low pressures for the sake of the facility to generate a large-area, uniform glow discharge plasma.…”
Section: Introductionmentioning
confidence: 99%